The hepatocyte growth factor/c-Met signaling pathway as a therapeutic target to inhibit angiogenesis - You, Weon-Kyoo (BMB Rep, 2008)
Angiogenesis in tumors is driven by multiple growth factors that activate receptor tyrosine kinases. An important driving force of angiogenesis in solid tumors is signaling through vascular endothelial growth factor (VEGF) and its receptors (VEGFRs). Angiogenesis inhibitors that target this signaling pathway are now in widespread use for the treatment of cancer. However, when used alone, inhibitors of VEGF/VEGFR signaling do not destroy all blood vessels in tumors and do not slow the growth of most human cancers. VEGF/VEGFR signaling inhibitors are, therefore, used in combination with chemotherapeutic agents or radiation therapy. Additional targets for inhibiting angiogenesis would be useful for more efficacious treatment of cancer. One promising target is the signaling pathway of hepatocyte growth factor (HGF) and its receptor (HGFR, also known as c-Met), which plays important roles in angiogenesis and tumor growth. Inhibitors of this signaling pathway have been shown to inhibit angiogenesis in multiple in vitro and in vivo models. The HGF/c-Met signaling pathway is now recognized as a promising target in cancer by inhibiting angiogenesis, tumor growth, invasion, and metastasis.